Entre a história e o legado : programa de referência e rede de proteção às crianças e adolescentes - Santos, Priscila Aguilera (2023)
Sexual Violence (SV) against children and adolescents is considered one of the most serious forms of violence committed against them. The victim, after disclosing the abuse suffered, is subjected to several procedures and services, in which she can relive the situation, which can cause her further suffering. In order to resist this scenario, programs and policies were created, with a protective role, as advocated by the ECA and the Federal Constitution/88. The present study is pioneering and its objective was to know the sociodemographic profile and to analyze the historical and assistance course of children and adolescents assisted in the Program of Assistance to Victims of Sexual Violence (PAVVS) of the Júlio Müller University Hospital (HUJM), in the city of Cuiabá - MT, having as specific objectives to characterize the population of children and adolescents assisted by the program, to describe the flow of assistance and to identify the importance of the PAVVS assistance within the Protection Network. To this end, this study used a quantitative and qualitative approach. We analyzed 565 medical records of children and adolescents from zero to 12 years of age, assisted in the period from 2008 to 2020. In addition, semi-structured interviews were conducted with three professionals, being a Psychologist, a Social Worker and a Pediatrician, who work or have worked in the PAVVS throughout the history of the institution. For the analysis of the quantitative results, descriptive statistical techniques were used. As for the results of the sociodemographic conditions, the majority of the victims were female (82.2%), living in peripheral neighborhoods, brown-skinned, chronically raped, in the intrafamily context, with, in most cases, the stepfather as the main suspect. Regarding the history of the PAVVS, the professionals interviewed said that the program was created around 2003, due to the need for a reference service for acute cases (up to 72 hours after the SA). Currently, the program receives all forms of SV (chronic and acute), providing outpatient, social and psychological care. Therefore, it can be considered that the service provides an important service within the protection network. Thus, it is expected that this study can contribute to the strengthening of the actors of the Protection Network and the management of the PAVVS, promoting the promotion of public policies of protection and confrontation of VS and the qualification of professionals of the PAVVS, besides serving as a basis for further research on this theme.